Integrated Nutrient Management for sustaining crop productivity - Singh, Avtar; Singh, Harmeet (Indian Farming, 2015)
The basic concept of integrated nutrient management (INM) or integrated plant nutrition management (IPNM) is the adjustment of plant nutrient supply to an optimum level for sustaining the desired crop productivity. It involves proper combination of chemical fertilizers, organic manure, crop residues, and N2 fixing crops and bio-fertilizers suitable to the system of land use and ecological, social and economic conditions. Integrated Nutrient Management (INM) refers to the practice of using optimum combination of different sources of nutrient supply for efficient crop production. This is achieved through optimization of benefits derived from different sources of nutrient supply including chemical fertilizers, organic manures, crop residues, green manures and Bio-fertilizers, which are desired as components of INM. Fertilizer consumption in India is grossly imbalanced since the beginning. In many areas the imbalanced fertilization is the root cause of poor crop yields and poor soil fertility status. In the agroecological regions cropping systems like rice-wheat, maize-wheat, ricepulse, potato-wheat and sugarcane demands immediate attention to correct the imbalances in nutrient consumptions to prevent further deterioration of soil quality and to break the yield barriers.